Irish general practitioner attitudes toward decriminalisation and medical use of cannabis: results from a national survey. Issue 1 (December 2017) - Crowley, Des; Collins, Claire; Delargy, Ide; Laird, Eamon; Van Hout, Marie
Abstract Background Governmental debate in Ireland on the de facto decriminalisation of cannabis and legalisation for medical use is ongoing. A cannabis-based medicinal product (Sativex®) has recently been granted market authorisation in Ireland. This unique study aimed to investigate Irish general practitioner (GP) attitudes toward decriminalisation of cannabis and assess levels of support for use of cannabis for therapeutic purposes (CTP). Methods General practitioners in the Irish College of General Practitioner (ICGP) database were invited to complete an online survey. Anonymous data yielded descriptive statistics (frequencies, percentages) to summarise participant demographic information and agreement with attitudinal statements. Chi-square tests and multi-nominal logistic regression were included. Results The response rate was 15% (n = 565) which is similar to other Irish national GP attitudinal surveys. Over half of Irish GPs did not support the decriminalisation of cannabis (56.8%). In terms of gender, a significantly higher proportion of males compared with females (40.6 vs. 15%;p < 0.0001) agreed or strongly agreed with this drug policy approach. A higher percentage of GPs with advanced addiction specialist training (level 2) agreed/strongly agreed that cannabis should be decriminalised (54.1 vs. 31.5%;p = 0.021). Over 80% of both genders supported the view that cannabis use has a significant effect on patients' mental health and increases the risk of schizophrenia (77.3%). Over half of Irish GPs supported the legalisation of cannabis for medical use (58.6%). A higher percentage of those who were level 1-trained (trained in addiction treatment but not to an advanced level) agreed/strongly agreed cannabis should be legalised for medical use (p = 0.003). Over 60% agreed that cannabis can have a role in palliative care, pain management and treatment of multiple sclerosis (MS). In the regression response predicator analysis, females were 66.2% less likely to agree that cannabis should be decriminalised, 42.5% less likely to agree that cannabis should be legalised for medical use and 59.8 and 37.6% less likely to agree that cannabis has a role in palliative care and in the treatment of multiple sclerosis (respectively) than males. Conclusions The majority of Irish GPs do not support the present Irish governmental drug policy of decriminalisation of cannabis but do support the legalisation of cannabis for therapeutic purposes. Male GPs and those with higher levels of addiction training are more likely to support a more liberal drug policy approach to cannabis for personal use. A clear majority of GPs expressed significant concerns regarding both the mental and physical health risks of cannabis use. Ongoing research into the health and other effects of drug policy changes on cannabis use is required.